2013
DOI: 10.1124/mol.113.089755
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Is a Novel Activator of AMP-Activated Protein Kinase and Decreases Liver Mass, Hepatic Fat Accumulation, and Serum Glucose in Obese Mice

Abstract: Valproic acid (VPA) is a widely prescribed anticonvulsant for the treatment of epilepsy. Here we demonstrate that VPA is a novel activator of AMP-activated protein kinase (AMPK), a key regulator of cellular metabolism, using primary mouse and human hepatocytes. Incubation of primary mouse hepatocytes with VPA resulted in increased levels of phosphorylated AMPK and acetylCoA carboxylase (ACC). This finding was recapitulated using primary human hepatocytes. Pretreatment of mouse hepatocytes with a small-molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…Several studies revealed the activation of AMPK related signaling pathway with non-specific HDAC inhibitors, MPT0E014 and VPA, in both type 1 diabetic rats and obese mice with several other metabolic variables (58, 60). However, the effect of the HDAC3 inhibitor on AMPK in the diabetic heart remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies revealed the activation of AMPK related signaling pathway with non-specific HDAC inhibitors, MPT0E014 and VPA, in both type 1 diabetic rats and obese mice with several other metabolic variables (58, 60). However, the effect of the HDAC3 inhibitor on AMPK in the diabetic heart remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported the integration of metabolite levels of bio fluids and other biochemical information (e.g., glucose and HbA1c) could better reflect T2DM risk than a single established risk factor [29,[39][40][41][42][43][44][45][46]. Determination of the levels of several amino acid and other metabolites that showed a marked change after metformin treatment could significantly improve drug response prediction and serve as markers for the diagnosis of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…119 Valproic acid, a potent antiepileptic agent, is effective in activating AMPK in vitro and in vivo. 120 Treatment of Lep ob/ob hyperphagic obese mice with valproic acid significantly reduced plasma glucose levels and decreased both liver mass and fat content, owing to AMPK activation. 120 Further studies will need to be conducted to define the role of these agents in activating AMPK in different stages of CKD.…”
Section: Mitochondrial Biogenesis and Kidney Diseasementioning
confidence: 98%